2014
DOI: 10.1186/s12876-014-0216-8
|View full text |Cite
|
Sign up to set email alerts
|

Early life environment and natural history of inflammatory bowel diseases

Abstract: BackgroundEarly life exposures may modify risk of inflammatory bowel diseases (IBD; Crohn’s disease (CD), ulcerative colitis (UC)). However, the relationship between early life exposures and natural history of IBD has not been previously examined.MethodsThis single center study included patients with CD or UC recruited in a prospective IBD registry. Enrolled patients completed a detailed environmental questionnaire that assessed various early life environmental exposures. Our primary outcome was requirement fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 47 publications
(45 reference statements)
1
17
0
2
Order By: Relevance
“…In addition, while we have previously shown that Paneth cell defects are induced in hypomorphic Atg16l1 mice after MNV infection, we are unable to yet identify such a link in CD patients (21). Even so, smoking is a clinically relevant environmental trigger (23,47). We show that the combination of relevant host genetic and environmental factors can provide insight into disease pathogenesis and therapeutic targets, as has been recently demonstrated in studies such as those of nonalcoholic fatty liver disease (48,49).…”
Section: (B) Significantly Downregulatedmentioning
confidence: 69%
“…In addition, while we have previously shown that Paneth cell defects are induced in hypomorphic Atg16l1 mice after MNV infection, we are unable to yet identify such a link in CD patients (21). Even so, smoking is a clinically relevant environmental trigger (23,47). We show that the combination of relevant host genetic and environmental factors can provide insight into disease pathogenesis and therapeutic targets, as has been recently demonstrated in studies such as those of nonalcoholic fatty liver disease (48,49).…”
Section: (B) Significantly Downregulatedmentioning
confidence: 69%
“…Comparable data were reported from a Danish cohort study, in which breastfeeding for more than six months decreased the odds of IBD (OR 0.50, 95%CI 0.23e1.11) [11]. Two further publications confirmed this relationship, one from the US and another from Asia-Pacific [12,13]. Breastfeeding for around six months or longer is desirable in all infants [14].…”
Section: Recommendationmentioning
confidence: 79%
“…Both factors indicate that hormonal influences also may play a role at least for the risk of disease flares. • For breastfeeding, conflicting results have been reported [20,[67][68][69][70][71] . A meta-analysis could not conclusively decide whether there is a protective or even diseaseaggravating effect [72] .…”
Section: Environmental Factors Known To Play a Role For Disease Flaresmentioning
confidence: 99%